2020
DOI: 10.1038/s41368-020-00092-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tertiary lymphoid structure and tumour infiltrating lymphocytes in oral squamous cell carcinoma

Abstract: Tertiary lymphoid structures (TLS) are ectopic lymphoid structures in cancers that are largely associated with favourable prognosis. However, the prognostic value of TLSs in oral squamous cell carcinoma (OSCC) is largely unknown, and the association between tumour infiltrating lymphocytes (TILs) and TLSs has been rarely explored in OSCC. In this study, associated markers of TLS, including peripheral node address (PNAd) in high endothelial venules, CD20 in B cells and CD3 in T cells, were examined in 168 OSCC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 47 publications
7
69
0
Order By: Relevance
“…CD8 + T cells have been shown to induce lipid peroxidation in cancer cells and sensitize cells to ferroptosis via IFNγ [ 40 ]. A higher density of these immune cells was found in tertiary lymphoid structure-positive patients and contributed to a better 5-year overall survival for OSCC [ 41 ]. Th2 cells and Tregs play a notable role in tumour immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…CD8 + T cells have been shown to induce lipid peroxidation in cancer cells and sensitize cells to ferroptosis via IFNγ [ 40 ]. A higher density of these immune cells was found in tertiary lymphoid structure-positive patients and contributed to a better 5-year overall survival for OSCC [ 41 ]. Th2 cells and Tregs play a notable role in tumour immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the presence of TLS was associated with increased 5 years overall-and relapse-free survival, and importantly, both immature and mature TLS conveyed equally positive outcomes. 58 In contrast, Posch et al (2018) delineated that TLS in colorectal tumors exhibited different degrees of maturation which were associated with differential prognostic values. 47 In particular, mature TLS containing germinal centers had a more positive prognostic outcome compared with immature TLS.…”
Section: Do Immature and Mature Tls Differentially Impact A Patient'smentioning
confidence: 99%
“…In addition, other gene signatures containing 8 and 19 genes related to the presence of T follicular helper cells, type 1 helper CD4 + T cells and B cells were reported in breast 54 and gastric 55 cancers. Collectively, this has led to the detection of TLS in lung, 41 , 45 , 56 , 57 oral squamous cell carcinoma, 58 breast, 54 , 59–61 colon, 51 , 62 stomach, 55 , 63 , 64 liver, 65 sarcoma, 3 , 66 , 67 bladder, 68 clear cell renal cell carcinoma, 4 ovarian cancer 46 , 69 and melanoma 4 , 5 , 15 , 44 , 50 , 70 ( Table 1 ). TLS formation and densities vary between tumor types, and between patients.…”
Section: Tertiary Lymphoid Structures In Cancer – Prognostic and Predmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies demonstrated that the tumor microenvironment is closely related to the prognosis and effectiveness of immunotherapy [45][46][47]. TLS is a crucial component of tumor immune microenvironment [5,48], which not only facilitating the recruitment of immune cells or play an anti-tumor role, but also act as a predictor for the prognosis of various cancer [4,7,10,15,22,24,34,39]. However, several studies reported the effect of TLS expression on prognosis and clinicopathological characteristics of solid tumor patient remains controversial [9,11,13,15].…”
Section: Discussionmentioning
confidence: 99%